Rozwiąż równanie i wykonaj sprawdzenie.
a) 4(x - 2) = 2(x - 3) +9
b) x + (2x - 7) - (2x + 1) = 5 -(x+6) c) 5(4x+3)=2(9x-1)-3(2x+1)+4 Plis szybko ​



Odpowiedź :

Szczegółowe wyjaśnienie:

rozwiązywanie w załączniku

Zobacz obrazek Zelaskoe

1.

a. (4-2x)-(x+3)=(x-5)+(-3-x)

4-2x-x-3=x-5-3-x

1-3x=-8

-3x=-9

x=3

 

b. (3-2x)+(3x+4)=-(3-2x)+(5x+4)

3-2x+3x+4=-3+2x+5x+4

7+x=1+7x

-6x=-6

x=1

 

c. -(x+3)+(2x-1)=(1+4x)+(3+x)

-x-3+2x-1=1+4x+3+x

x-4=4+5x

-4x=8

x=-2

 

d. -(x+3)-(2x+8)=(-3-2x)+(2x+1)

-x-3-2x-8=-3-2x+2x+1

-3x-11=-2

-3x=9

x=-3

2.

a. (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)

3-2x-x-4-2x-5=3x-4-5x-7

-6-5x=-2x-11

-3x=5

x=-

x=-1

 

b. (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)

4-x-2x-3+x-4=-2x+3-x-7

-3-2x=-3x-4

x=-1

 

c. (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)

4x-5+x-7-2x+8=-3x+4-x-6

3x-4=-4x-2

7x=2

x=

 

d. -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)

-4+2x-2x-4=3x-1+2x-5-7-3x

-8=2x-13

-2x=-5

x=

x=2

 

3.

a. 3(x-4)-4(2x-7)=2(x+5)

3x-12-8x+28=2x+10

-5x+16=2x+10

-7x=-6

x=

 

b. 2(2x-3)+3(4-x)=-(x+1)

4x-6+12-3x=-x-1

x+6=-x-1

2x=-7

x=-

x=-3

 

c. 2(x-3)-4(3+x)=-3(x+2)+2(2x-1)

2x-6-12-4x=-3x-6+4x-2

-2x-18=x-8

-3x=10

x=-

x-3

 

d. 6(x+1)+3(2-x)=2(2x-1)-(4-x)

6x+6+6-3x=4x-2-4+x

3x+12=5x-6

-2x=-18

x=9

 

4.

a.  2(x-7)-3(x+2)=4(x+3)+2(x-9)

2x-14-3x-6=4x+12+2x-18

-x-20=6x-6

-7x=14

x=2

 

b. -3(x+6)-6(2x+8)=-2(4-x)+9(x+8)

-3x-18-12x-48=-8+2x+9x+81

-15x-66=11x+73

-26x=139

x=-

x=-5

c. -8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)

-8x-16+3x+15=-4x-6+8x-4

-5x-1=4x-10

-9x=-9

x=1

 

d. 6(4-x)+5(2x-5)=4(x-1)-3(4-x)

24-6x+10x-25=4x-4-12+3x

4x-1=7x-16

-3x=-15

x=5

 

5.

a. 3(3-x)+2x=8-2(x-1)

9-3x+2x=8-2x+2

9-x=10-2x

x=1

b. 4x+5-(3x+6)=2(2+x)-4

4x+5-3x-6=4+2x-4

x-1=2x

-x=1

x=-1

 

c. 4-5(3-x)=-x-(3-2x)

4-15+5x=-x-3+2x

-11+5x=x-3

4x=8

x=2

 

d. x-(7+2x)=2(x-1)+1

x-7-2x=2x-2+1

-x-7=2x-1

-3x=6

x=2